Implementasi Asas Keterbukaan Dalam Pembuatan PERPPU Nomor 2 Tahun 2022 Tentang Cipta Kerja (UU Omnibus Law) - Sari, Dita Indah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The Job Creation Law ultimately gave rise to a statement that it did not fulfill the principle of openness in the law formation process. The replacement regulation, namely "Perppu Number 2 of 2022 concerning Job Creation" also still does not apply the principle of openness even in the process of its formation and ratification. This is the basis for writing this research by discussing the implementation that should be carried out if it is connected to the principle of openness that exists in the process of forming and ratifying laws. This research uses a juridical-normative type with a statutory approach. The author uses primary and secondary legal materials originating from statutory regulations, doctrine, legal articles, and several previous studies that are relevant to the research topic. The conclusion that the author conveys is that it is important to place society at the top of the constitution where they have the right to know and take part in the process of making legal products.